EFFECT OF TERTIARY SHOOT PRUNING AND FOLIAR SPRAY OF NUTRIENTS ON FLOWERING AND YIELD OF CASHEW (ANACARDIUM OCCIDENTALE L.) UNDER HIGH DENSITY PLANTING SYSTEM - K. MURALI; P. PRASANNA KUMAR; M. S. ANEESA RANI (The Bioscan, 2015)
A field experiment was conducted during 2011-2012 at Regional Research Station, TNAU, Vriddhachalam. The experiment was laid out in split plot design with main plot consisted of tertiary shoot pruning (M1) and control (M2). The sub plot consisted of foliar spray of NPK 19:19:19 (1%) was given at new flush stage uniformly in all the treatments except the control in M1S9 and absolute control in M2S9 (August). A second spray of NPK 19:19:19 (1%), boron (0.1%), sulphate of potash (SOP) (2 %), mono ammonium phosphate (MAP) (1%) alone or in different combinations were given at flowering stage (December). The results also revealed that the treatment (M1S8) consisting of tertiary shoot pruning along with two foliar sprays viz., NPK 19:19:19 @ one per cent at new flush stage (August) followed by a second spray of boron 0.1% + SOP 2% + MAP 1% at flowering stage (December) was found to be the best in increasing number of current season’s shoot (3.25 Numbers), number of panicles (16.3 Numbers per m2), percentage of bisexual flowers (31.9%), percentage of fruit set (11.5%) and yield (4.43 kg/ tree) in cashew grown under high density planting system.